Pro-survival Function of Akt/Protein Kinase B in Prostate Cancer Cells - Hitesh Thakkar; Xufeng Chen; Frazier Tyan; Suzanna Gim; Heather Robinson; Calvin Lee; Sanjay Pandey; Chichi Nwokorie; Nneka C. Onwudiwe; Ruchi Srivastava (2001)
Tumor necrosis factor superfamily member TRAIL/Apo-2L has recently been shown to induce apoptosis in transformed and cancer cells. Some prostate cancer cells express constitutively active Akt/protein kinase B due to a complete loss of lipid phosphatase PTEN gene, a negative regulator of phosphatidylinositol 3-kinase pathway. Constitutively active Akt promotes cellular survival and resistance to chemotherapy and radiation. We have recently noticed that some human prostate cancer cells are resistant to TRAIL. We therefore examined the intracellular mechanisms of cellular resistance to TRAIL. The cell lines expressing the highest level of constitutively active Akt were more resistant to undergo apoptosis by TRAIL than those expressing the lowest level. Down-regulation of constitutively active Akt by phosphatidylinositol 3-kinase inhibitors, wortmannin and LY294002, reversed cellular resistance to TRAIL. Treatment of resistant cells with cycloheximide (a protein synthesis inhibitor) rendered cells sensitive to TRAIL. Transfecting dominant negative Akt decreased Akt activity and increased TRAIL-induced apoptosis in cells with high Akt activity. Conversely, transfecting constitutively active Akt into cells with low Akt activity increased Akt activity and attenuated TRAIL-induced apoptosis. Inhibition of TRAIL sensitivity occurs at the level of BID cleavage, as caspase-8 activity was not affected. Enforced expression of anti-apoptotic protein Bcl-2 or Bcl-XLinhibited TRAIL-induced mitochondrial dysfunction and apoptosis. We therefore identify Akt as a constitutively active kinase that promotes survival of prostate cancer cells and demonstrate that modulation of Akt activity, by pharmacological or genetic approaches, alters the cellular responsiveness to TRAIL. Thus, TRAIL in combination with agents that down-regulate Akt activity can be used to treat prostate cancer.